2001
DOI: 10.1177/089826430101300306
|View full text |Cite
|
Sign up to set email alerts
|

Mobility Impairments in Crash-Involved Older Drivers

Abstract: We examined associations of functional impairments with vehicle crashes using telephone interviews of 244 elderly at-fault crash involved Mobile County, Alabama, drivers and 475 crash free controls, frequency matched on age and gender. Police-investigated crash reports filed in 1996 were obtained from the Alabama Department of Public Safety. After controlling for potential 43

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…Several studies have associated driving difficulties among older adults with physical measures of mobility and balance (Lyman et al, 2001;Marottoli et al, 1994;Marottoli and Drickamer, 1993;Sims et al, 2001). The present exercise intervention showed that it is possible to improve movement speed, which is confirmed by the results of the Foot Tap Test and also by the reduced movement time in the simple and dual-task conditions.…”
Section: Discussionsupporting
confidence: 81%
“…Several studies have associated driving difficulties among older adults with physical measures of mobility and balance (Lyman et al, 2001;Marottoli et al, 1994;Marottoli and Drickamer, 1993;Sims et al, 2001). The present exercise intervention showed that it is possible to improve movement speed, which is confirmed by the results of the Foot Tap Test and also by the reduced movement time in the simple and dual-task conditions.…”
Section: Discussionsupporting
confidence: 81%
“…This is due both to older drivers' higher likelihood of being involved in a police-reported crash per VMT and to their greater odds of dying when involved in a crash (Cicchino and McCartt, 2014;Li et al, 2003). Age-related declines in cognitive, visual, and physical functioning can heighten an older driver's crash risk (Anstey et al, 2005;Owsley et al, 1998;Sims et al, 2001;Stutts et al, 1998).…”
Section: Introductionmentioning
confidence: 96%
“…Carr, Flood, Steger-May, Schechtman, and Binder (2006) found that despite the presence of physical frailty, 85% of community-dwelling older adults continued to drive distances comparable to those of the general older-adult population. Crash-involved older drivers are significantly more likely to report difficulty walking a quarter mile and carrying heavy objects, and are more likely to report having a fall within the past year (Sims, McGwin, Pulley, & Roseman, 2001), underscoring the importance of maintaining physical fitness for driving. Results of the current study suggest that targeted exercises may improve the functional capacity of older drivers in areas required for driving, especially with regard to the upper body flexibility needed for shoulder checking and visual scanning, the hand reaction time needed for steering and responding to emergencies, and the endurance required for prolonged driving distances.…”
Section: Discussionmentioning
confidence: 98%